Mass communication sciences in the Maghreb: a hybrid identity for an evolving discipline - Hamidou, Kamal (Penerbit Universiti Kebangsaan Malaysia, 2016)
Throughout the world, mass communication sciences had faced many difficulties to impose itself in the academic and administrative spheres as a new, entirely independent discipline. Even nowadays, certain fierce opponents still refuse to admit that it is a discipline, claiming that it is only a field. Indeed the discipline is now established and well recognized in the major countries of the world, but it did not undertake the same path in all parts of the world. This article discusses the issue of Mass Communication Sciences’ state in Maghreb. It focuses on the historical, political, academic and administrative considerations which influenced its progress in three countries, namely: Algeria, Tunisia and Morocco. The purpose is to identify the influences that marked the advent and development of the discipline in the region. The study found out that Mass Communication Sciences in the Maghreb suffered from the lack of visibility on its identity; this is essentially due to the name given to the discipline ‘Information and Communication Sciences’, inherited from the French administration as the former colonizing or protective state of the three countries. The study also highlights the ambiguity which accompanied the establishment of a discipline that first emerged from the reduced ‘journalism’ appellation, and finds itself secondly considered as a simple branch of Political Sciences, which poses the question of its legitimacy in academic decision makers’ minds. Finally, the study underlines the impact of the absence of professional associations able to defend the interests of the discipline and to represent it within the different administrative or academic decision levels, either in the three single countries or at a regional level.